Teaching Anxiety, Stress and Resilience During the COVID-19 Pandemic: Evaluating the Vulnerability of Academic Professionals in Mexico Through the Adapted COVID-19 Stress Scales - Juan Luis Delgado-Gallegos; Gerardo R. Padilla-Rivas; Erika Zuñiga-Violante; Gener Avilés-Rodriguez; Daniel Arellanos-Soto; Hector Franco Villareal; María de los Ángeles Cosío-León; Gerardo Salvador Romo-Cardenas; Jose Francisco Islas (Frontiers Media S.A., 2021)
To mitigate the COVID-19 infection, many world governments endorsed the cessation of non-essential activities, such as the school attendance, forcing a shift of the teaching model to the virtual classroom. From this shift, several changes in the teaching paradigm derived, in addition to the COVID-19 pandemic, which could have an impact in academic professional's mental health. In the present work we show the application of a modified version of the adapted COVID-19 stress scales (ACSS) which also included teaching anxiety and preparedness, and resilience for academic professionals in Mexico. These scales were applied during the unprecedented transformation of the education system undergone in the COVID-19 quarantine. Most of the studied variables: gender, age, academic degree, household occupants, having a disease, teaching level, teaching mode, work hours, resilience, teaching anxiety and preparedness, and fear of being an asymptomatic patient (FOBAP), showed significant statistical correlation between each other (p < 0.050) and to the 6 areas of the ACSS (danger, contamination, social economical, xenophobia, traumatic stress, and compulsive checking). Our results further showed that the perceived stress and anxiety fell into the category of Absent to Mild, with only the danger section of the ACSS falling into the Moderate category. Finally, the resilience generated throughout the quarantine was very high, which seems to be a predictor of adaptation the academic professional has undergone to cope with stress.